Cultural and environmental values in the arcaded Mesaorian houses of Cyprus - Dinçyürek, Özgür; Mallick, Fuad; Numan, İbrahim (Elsevier, 2003)
The central Mesaorian region of Cyprus is the context for the development of a house form unique to the region. This article discusses the forces that influenced their evolution and the resulting typological developments. They are analyzed in terms of their functional characteristics, use patterns, and variations of the basic form. Thermal data suggests optimization of climatic forces. These adobe houses are currently facing oblivion due to changes in lifestyle and shift in priorities. They, however, present a case from which lessons can be learnt and adopted to the modern context for a meaningful and appropriate architecture in the region.
Due to copyright restrictions, the access to the publisher version (published version) of this article is only available via subscription. You may click URI and have access to the Publisher Version of this article through the publisher web site or online databases, if your Library or institution has subscription to the related journal or publication.
Keywords: Environment, Mesaorian houses, Typology, Culture; Adobe, Vernacular, Lifestyle, ENGINEERING; ENVIRONMENTAL, environment, typology, lifestyle, adobe; CIVIL, CONSTRUCTION & BUILDING TECHNOLOGY, vernacular, culture